2014
DOI: 10.2337/dc13-2717
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Incidence of Diabetes in Pregnancy and Serious Perinatal Outcomes: A Large, Population-Based Study in Ontario, Canada, 1996–2010

Abstract: OBJECTIVEWomen with diabetes in pregnancy have high rates of pregnancy complications. Our aims were to explore trends in the incidence of diabetes in pregnancy and examine whether the risk of serious perinatal outcomes has changed. RESEARCH DESIGN AND METHODSWe performed a population-based cohort study of 1,109,605 women who delivered in Ontario, Canada, between 1 April 1996 and 31 March 2010. We categorized women as gestational diabetes (GDM) (n = 45,384), pregestational diabetes (pre-GDM) (n = 13,278), or no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
219
3
8

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 305 publications
(238 citation statements)
references
References 34 publications
8
219
3
8
Order By: Relevance
“…The incidence of congenital anomalies in infants of diabetic women is 4-10 times higher than that in non-diabetic population. It depends on metabolic compensation of DM (3,14,25,26). This fact was also demonstrated in our study, where in diabetic women with preparation for pregnancy, the frequency of congenital cardiac anomalies was 18 %, whereas in those without preparation for preg-nancy, it was 30 %.…”
Section: Discussionsupporting
confidence: 82%
“…The incidence of congenital anomalies in infants of diabetic women is 4-10 times higher than that in non-diabetic population. It depends on metabolic compensation of DM (3,14,25,26). This fact was also demonstrated in our study, where in diabetic women with preparation for pregnancy, the frequency of congenital cardiac anomalies was 18 %, whereas in those without preparation for preg-nancy, it was 30 %.…”
Section: Discussionsupporting
confidence: 82%
“…Since the mid-1990s, in parallel with the global increase in all forms of diabetes [1], regional [3,4] and national [5][6][7] data have demonstrated an increase in the proportions of pregnancies complicated by diabetes. In much of the world, a greater proportion of pregnant women with diabetes antedating pregnancy have type 2 diabetes, and the increase in the prevalence of diabetes during pregnancy is greater for type 2 (111-354%) than for type 1 (33-162%) diabetes [6][7][8] .…”
Section: Introductionmentioning
confidence: 99%
“…Populationbased studies examining trends in adverse pregnancy outcomes over long periods are sparse and there appears to be some discrepancy in findings. For example, one study [3] found an apparent decline in neonatal congenital malformations over time while another [8] did not. Likewise, a decrease in stillbirths over time was previously reported by one research group [8] but no differences were observed in another study [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Presently, the prevalence of type 1 diabetes in pregnancy is increasing along with type 2 and gestational diabetes [8][9][10]. Several studies have evaluated the clinical relevance of White's classification [7,[11][12][13].…”
Section: Introductionmentioning
confidence: 99%